Contraceptive discontinuation and repeat unintended pregnancy within 1 year after an abortion - Upadhyay, Ushma D. (2011)
BACKGROUND: We examined 12-month hormonal contraceptive continuation and pregnancy rates by abortion history. STUDY DESIGN: Women who wanted to avoid pregnancy for at least one year were recruited at four San Francisco Bay area family planning clinics on regular service days and on abortion care days. Participants completed baseline and follow-up questionnaires. Multivariable Cox models assessed the factors associated with method discontinuation and pregnancy. RESULTS: Women who were enrolled into the study on the day of their abortion were 20% more likely to discontinue their contraceptive method than women who never had an abortion (AHR=1.21; 95%CI=1.03-1.42). Women who had a recent abortion or previous abortion were 60% more likely to have a pregnancy during follow-up than women who never had an abortion (AHR=1.63, 95%CI=1.21-2.20 and AHR=1.66, 95%CI=1.18-2.33, respectively). CONCLUSION: The experience of having an unintended pregnancy and abortion does not lead to behavioral changes that protect against another unintended pregnancy.